Distinctive behavioral and cellular responses to fluoxetine in the mouse model for Fragile X syndrome - Uutela, Marko; Lindholm, Jesse; Rantamäki, Tomi; Umemori, Juzoh; Hunter, Kerri; Võikar, Vootele; Castrén, Maija L. (Frontiers in Cellular Neuroscience, 2014)
Fluoxetine is used as a therapeutic agent for autism spectrum disorder (ASD), including Fragile X syndrome (FXS). The treatment often associates with disruptive behaviors such as agitation and disinhibited behaviors in FXS. To identify mechanisms that increase the risk to poor treatment outcome, we investigated the behavioral and cellular effects of fluoxetine on adult Fmr1 knockout (KO) mice, a mouse model for FXS. We found that fluoxetine reduced anxiety-like behavior of both wild type and Fmr1 KO mice seen as shortened latency to enter the center area in the open field test. In Fmr1 KO mice, fluoxetine normalized locomotor hyperactivity but abnormally increased exploratory activity. Reduced Brain-derived neurotrophic factor (BDNF) and increased TrkB receptor expression levels in the hippocampus of Fmr1 KO mice associated with inappropriate coping responses under stressful condition and abolished antidepressant activity of fluoxetine. Fluoxetine response in the cell proliferation was also missing in the hippocampus of Fmr1 KO mice when compared with wild type controls. The postnatal expression of serotonin transporter was reduced in the thalamic nuclei of Fmr1 KO mice during the time of transient innervation of somatosensory neurons suggesting that developmental changes of serotonin transporter (SERT) expression were involved in the differential cellular and behavioral responses to fluoxetine in wild type and Fmr1 mice. The results indicate that changes of BDNF/TrkB signaling contribute to differential behavioral responses to fluoxetine among individuals with ASD.